2002
DOI: 10.1021/np020098q
|View full text |Cite
|
Sign up to set email alerts
|

Panepophenanthrin, from a Mushroom Strain, a Novel Inhibitor of the Ubiquitin-Activating Enzyme

Abstract: Screening for inhibitors of the ubiquitin-proteasome pathway, considered to regulate important cellular events and linked to serious diseases as well, led to isolation of a new compound, panepophenanthrin, from the fermented broth of a mushroom strain, Panus rudis Fr. IFO 8994. This is the first inhibitor of the ubiquitin-activating enzyme, which is indispensable for the ubiquitin-proteasome pathway. The structure of panepophenanthrin was determined by NMR and X-ray crystallographic analyses as 1,3a,10-trihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 14 publications
1
68
0
Order By: Relevance
“…Such poor correlation suggested that the proposed structure was in error, though the real identity of hexacyclinol had to be solved. To make progress in this regard, Rychnovsky 65 became interested in panepophenanthrin (135), isolated in 2002 from a different strain of Panus rudis, 66 and synthesized by several research groups. 67 Despite the ring systems of 134 and 135 bear no relationship, both display similar functional groups, molecular weights and biological source.…”
Section: Hexacyclinolmentioning
confidence: 99%
“…Such poor correlation suggested that the proposed structure was in error, though the real identity of hexacyclinol had to be solved. To make progress in this regard, Rychnovsky 65 became interested in panepophenanthrin (135), isolated in 2002 from a different strain of Panus rudis, 66 and synthesized by several research groups. 67 Despite the ring systems of 134 and 135 bear no relationship, both display similar functional groups, molecular weights and biological source.…”
Section: Hexacyclinolmentioning
confidence: 99%
“…These results clearly showed that both a 4-pyrone ring and unit X (C-1′-C-5′) were essential to inhibit formation of the E1-ubiquitin intermediate and confirmed the previous result that himeic acid A (1), but not B (2) or C (3), inhibited E1 activity. 7) Despite many attempts to develop E1 inhibitors, only four natural inhibitors, panapophenanthorine, 10) himeic acid A, 7) largazole, 11) and hyrtioreticulin A, 8) and two synthetic inhibitors, PYR-41 12) and NSC624206, 13) have been discovered so far. Among them, PYR-41 is cell-permeable and blocks protein degradation and cytokine-induced activation of nuclear factorkappa B (NF-κB), which leads to the activation of p53 in cells and death of cells transformed with wild-type p53.…”
Section: )mentioning
confidence: 99%
“…The mushroom isolate panepophenanthrin 47 and the Aspergillus isolate himeic acid A 48 were both demonstrated to inhibit ubiquitin activation by recombinant E1 in vitro, though neither study reports cellular activity and their mechanisms of action remain unclear. Weissman and colleagues have isolated a small molecule cell permeable E1 inhibitor, PYR-41, in a larger screen intended to identify inhibitors of Mdm2 ligase activity.…”
Section: Ubiquitin E1 and E2 As Molecular Targetsmentioning
confidence: 99%